The corporate accountability of Damansara Realty Berhad towards its stakeholders / Muhammad Hafiz Abd Malek and Mohd Izmer Md Aris - Abd Malek, Muhammad Hafiz; Md Aris, Mohd Izmer (Faculty of Business and Management, Universiti Teknologi MARA, 2013)
In reality, accountability nowadays has been a huge major concern in each company and organizations worldwide. Somehow it can affect the organization performance and also its social response towards the key player liable in the company and other external factor as well. Behind the successful business that we can see nowadays, somehow they implement the accountability between every sorts of view especially that are networked with the business. It is judgmental to say that each business out there needs to understand and apply the mentioned principle in order to maintain its operations as a whole. Theories regarding accountability whether in every sectors have much being debated in order for clear explanation and deep understanding can be supplied and practiced. Therefore, in this research paper we examine the accountability that exists and yet being practiced within the organization towards their stakeholders. This study was undertaken to address the gap that exist in the research and literature specific towards the company we chose and also comparing both to form an analysis. Furthermore, we use stakeholders as a mechanism for our study to measure the gap arises during examining the data obtained. As part of the research, we should understand the existence of corporate and accountability in order to monitor the above statement. Efficiency and accountability of stakeholders seems to be the key factor of an organizations moving forward. It is essentials in setting of a corner-stone of accountability in terms of the performance and organizational success (Takaki, 2005). While corporate stands above in some sectors, more demanding accountability that the most we can see. According to Özkan (2012), corporate sector is one of the sectors these days that implement accountability where the importance of accountability are being one of the priority in providing the basic social needs. Every successful business has to understand and apply the mentioned principle so as to provide the business performance and maintain its operations. The development determining corporate behaviour is a fascinating topic, offering insight into the societal problems of corporate enterprise as they are related to their accounting, their administration, and their external reporting (Filios, 1984). As corporate accountability plays an important role in an organization, each component is reliable for a company to maintain its process of the whole business operations. According to Wikipedia, corporate accountability can be referred as the act of being accountable to the stakeholders of an organization, which may include shareholders, employees, suppliers, customers, and even the local community or society. In fact, the primary stakeholders provide the best accountability perspective because their goals reflect, generally, the largest section of the community. According to Unerman & O’Dwyer (2007), nowadays there are tonnes of issues that are related to social and environmental accountability and yet have been studied widely, with studies developing a range of theoretical explanations for motivations underlying corporate accountability practices, empirically investigating current practices, and/or suggesting ways to improve accountability mechanisms. With this, by analyzing the company act with the theory suggested, we should be able to examine the data and comparing them as in proving whether the theory is reliable in finding the gap if arises in this case.